Pengaruh Media Bahan Bekas Kemasan Terhadap Kemampuan Literasi Dan Numerasi Pada Anak Kelompok B Di TK DWP Pademonegoro Sukodono Sidoarjo - Ainul Khoirunnisa; Hendratno; Sri Setyowati (LP. Ma'arif Janggan Magetan, 2023)
This study aims to determine the effect of used packaging media on group B children's literacy and numeracy abilities in the Pademonegoro Unitary Dharma Wanita Kindergarten, Sukodono District, Sidoarjo Regency. This research is motivated by the results of preliminary observations, which show that most children experience obstacles in recognizing letters and numbers. The research took place through a quantitative approach with an experimental design. The experimental design model used is the Quasi Experiment Model with one kind of treatment. The research subjects were 68 children aged 5-6 in Pademonegoro Dharma Wanita Kindergarten. The experimental group consisted of 17 children in group B (Sun) and 17 in group B (Rainbow). The control group consisted of 17 children in group B (Stars) and 17 in group B (Months). The research data was collected through observation techniques, documentation and research instruments. The research data was analyzed statistically using parametric statistical tests, namely the paired t-test with a significant level (sig) less than 5% (0.05). The data analysis results showed an influence of used packaging materials on the literacy and numeracy abilities of group B children in Pademonegoro Unity Dharma Wanita Kindergarten, Sukodono District, Sidoarjo Regency. This research implies that educators are expected to be able to maximize this learning media as a varied learning resource during the implementation of the independent curriculum and as a reference source because learning media is more natural and fun in learning by using media that is easily available and children can explore and collaborate.